Finite element analysis and biomechanical study of “sandwich” fixation in the treatment of elderly proximal humerus fractures - Lv, Yang; Zhang, Ziyan; Qv, Ji; Sheng, Qian; Zhang, Jian; Piao, Chengdong (Frontiers in Bioengineering and Biotechnology, 2024)
Proximal humerus fractures (PHFs) are common in the elderly and usually involve defects in the medial column.The current standard for medial column reconstruction is a lateral locking plate (LLP) in combination with either an intramedullary fibula support or an autogenous fibula graft. However, autogenous fibula graft can lead to additional trauma for patients and allogeneic fibular graft can increase patients’ economic burden and pose risks of infection and disease transmission. The primary objective of this study was to introduce and assess a novel “Sandwich” fixation technique and compare its biomechanical properties to the traditional fixation methods for PHFs. In this study, we established finite element models of two different internal fixation methods: LLP-intramedullary reconstruction plate with bone cement (LLP-IRPBC) and LLP-intramedullary fibula segment (LLP-IFS). The biomechanical properties of the two fixation methods were evaluated by applying axial, adduction, abduction, torsional loads and screw extraction tests to the models. These FEA results were subsequently validated through a series of biomechanical experiments. Under various loading conditions such as axial, adduction, abduction, and rotation, the LLP-IRPBC group consistently demonstrated higher structural stiffness and less displacement compared to the LLP-IFS group, regardless of whether the bone was in a normal (Nor) or osteoporotic (Ost) state. Under axial, abduction and torsional loads, the maximum stress on LLPs of LLP-IRPBC group was lower than that of LLP-IFS group, while under adduction load, the maximum stress on LLPs of LLP-IRPBC group was higher than that of LLP-IFS group under Ost condition, and almost the same under Nor condition. The screw-pulling force in the LLP-IRPBC group was 1.85 times greater than that of the LLP-IFS group in Nor conditions and 1.36 times greater in Ost conditions. Importantly, the results of the biomechanical experiments closely mirrored those obtained through FEA, confirming the accuracy and reliability of FEA. The novel “Sandwich” fixation technique appears to offer stable medial support and rotational stability while significantly enhancing the strength of the fixation screws. This innovative approach represents a promising strategy for clinical treatment of PHFs.